Factors Influencing the Price of Chile Piquin wild Chili (Capsicum annuum L. var. Glabriusculum) of North-east Mexico - Villalon-Mendoza, Horacio; Medina-Martinez, Teodoro; Ramirez-Meraz, Moises; Solis Urbina, Sandra Elizabeth; Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2014)
In order to understand the factors influencing the great demand and also the high cost of piquin pepper (Capsicum annuum L. var. glabriusculum Heiser & Pickersgill) in north-eastern Mexico, surveys were undertaken in the study area. This was done to determine the factors that make people to pay a high price for piquin pepper. The results showed with 95% confidence, that its desirable flavor compared to that of other chilis like serrano and jalapeno, was the main reason for the consumer to pay more for the piquin pepper in the market. Hence it is considered a premium product for which people pay on average US$ 6.25±3.75 for one pound of piquin pepper